Sistem Informasi Manajemen Aset (SIMASET) Berbasis Web - Herdian Afrody; Wida Prima Mustika; Andi Sanjaya (LPPM STIKOM Tunas Bangsa, 2023)
Assets are the most important resource for an individual or an organization that owns them, because assets are tools that support the activities of an organization. As time goes by the assets in the company will experience many changes (increase and decrease) that apply very quickly and that also happens to PT. Asiamadya Selaras. To support operational activities, PT. Asiamadya Selaras still uses a semi-computerized system, namely using Microsoft Excel in managing existing assets. This is less efficient in terms of time, effort and cost. As technology continues to develop, it can be used to overcome some of the obstacles currently faced, such as by creating a system that assists in asset management to prevent data damage or loss. Web-based system development is used with system modeling, namely UML (Unified Modeling Language), including use case, activity, class, and sequence diagrams. The asset management system development methodology uses the waterfall model, PHP programming with the Laravel framework, and MySQL database.